STRESS ANALYSIS EVALUATION AND PIPE SUPPORT TYPE ON HIGH-PRESSURE AND TEMPERATURE STEAM PIPE - Aswin, Aswin; Hasnan, Ahmad (International Journal of Mechanical Engineering Technologies and Applications, 2023)
The design and analysis of piping systems are critical in the power and process industries. The steam pipe is one of the main requirements for the plant to be installed. High-pressure and high-temperature steam pipes in the piping system are critical lines that need to be subjected to stress analysis. This study aims to evaluate the stress and the effect of using pipe supports on the stress in the piping system. Stress analysis is needed to ensure that the piping system that is designed is safe and does not exceed the allowable stress under operating conditions. Data analysis used ASTM A335-P11 as a pipe material with a design pressure of 65 bars and a design temperature of 480 °C. Stress analysis was carried out using CAESAR II software, which refers to ASME B31.3 process piping standards and codes. The findings revealed that the type of support chosen, such as the gap and distance of pipe support, has a significant impact on the stress value in the piping system. The results of the analysis are carried out several times to get the stress value so that it does not exceed the allowable stress. The greatest stress value occurs at the expansion load condition in the steam pipe system design. The chosen piping system design has a ratio of 93.6%, which is located at node 220 with a stress value of 35889.1 psi and an allowable stress of 38327.2 psi. Because the stress value that occurs is below the allowable stress, the steam pipe system is safe to be installed and operated.